Association of cognitive health status with happiness, helplessness and hopelessness in different races: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Umucu, Emre; Wyman, Mary F; Lee, Beatrice; Zuelsdorff, Megan; Lambrou, Nickolas H; Johnson, Adrienne L; Bouges, Shenikqua; James, Taryn T; Salazar, Hector; Simó, Carola A Ferrer; Carter, Fabu P; Asthana, Sanjay; et al.
Abstract: Background: Cognitive impairments are linked to changes in positive and negative affect. However, it remains unclear whether some dimensions of positive and negative affect are associated with cognitive health status (CHS) and the relationships between pillars of positive and negative affects and CHS function similarly across racial groups. In this study, we tested whether (a) happiness, helplessness, and hopelessness are linked to CHS and (b) if these relationships are similar among blacks and whites. Methods: Participants were 755 enrollees in the Wisconsin ADRC who had normal cognition, MCI, and dementia at baseline. The majority of participants were female (59.2%) and Caucasian (81.5%). The average age at baseline was 64.23 ( SD =10.40).CHS was categorized as cognitively normal, mild cognitive impairment, and dementia. Happiness, helplessness, and hopelessness were measures with three items from the 15‐item Geriatric Depression Scale . For question (a), all races were included in the analyses. For question (b), blacks and whites are subgrouped and all other races were excluded. Chi‐square or Fisher's Exact tests were conducted to test our research hypotheses. Results: Chi‐square test results revealed that (a) an association between happiness and CHS, χ 2 (2)=6.06, p <.05, (b) an association between helplessness and CHS, χ 2 (2)=6.44, p <.05, and (c) an association between hopelessness and CHS, χ 2 (2)=14.11, p <.01. The association of happiness with CHS remained significant in blacks (Fisher's exact=.03), but not in whites, χ 2 (2)=1.04, p =.59. The association of helplessness with CHS was not significant for blacks (Fisher's exact = 1.00), but was significant for whites, χ 2 (2)=8.47, p < .05. Finally, the relationship between hopelessness and CHS was not associated in blacks (Fisher's exact=.19), but was in whites, χ 2 (2)=16.31, p <.01. Conclusion: Race differences in the association of CHS and happiness, helplessness, and hopelessness were found. For blacks, only happiness was significantly associated with CHS, whereas, for whites, CHS was associated with helplessness and hopelessness, but not with happiness. These findings can inform the development of culturally‐tailored interventions to prevent cognitive decline for specific races.